Primary pituitary abscess presenting as cystic pituitary adenoma - Watcharasaksilp, Wanarak; Limpastan, Kriengsak; Norasathada, Tanya; Vaniyapong, Tanat (Biomedical Sciences and Clinical Medicine, 2024)
Pituitary abscess is a potentially life-threatening and rare condition. This report presents the case of a young male who was investigated for progressive headache. Magnetic Resonance Imaging (MRI) showed a cystic sellar lesion with ring enhancement that was diagnosed fi rstly as cystic pituitary adenoma. The patient was operated on with a sublabial transphenoidal approach to the pituitary gland. After dural opening, yellowish purulent material was obtained, with no tumor tissue detected. Pus examination showed many white blood cells (WBC) and gram positive diplococci. Culture was negative. After surgery, the patient was given antibiotics for 6 weeks and he made a good recovery.